Elliptic curve coding technique application for digital signature - BULDU, ALİ; YILDIZ, KAZIM (WILEY-HINDAWI, 2016)
An elliptic curve coding technique application is proposed in this study. It is one of the asymmetric coding techniques and so crucial in today's world. The application codes messages between two different console screens by using elliptical curve coding technique. It is created by using C# with the class of Crypto Next Generation (CNG) which brings into consideration the messaging system as four different security levels. The aim is to use the necessary additional security precautions when using asymmetric techniques. Cryptography techniques are not used for connection, and messaging occurs in security level 1. Security level 2 describes the public channel for the connection between two console screens which is used for sending and receiving key pair; then messaging occurs. Public channel for the connection between two console screens is used for sending and receiving signed key pair and encrypted data; then messaging occurs in security level 3. Security level 4 is the safest one. A private channel for the connection between two console screens is used for sending and receiving a signed key pair and encrypted data, and then messaging occurs. In addition, Advanced Encryption Standard (AES) technique is used in applications which is one of the symmetric cryptographic techniques for encrypting data. Copyright (C) 2016 John Wiley & Sons, Ltd.
Keywords: cryptology; elliptic curve coding; digital signature; security